(The Segmentation of Industrial Market and its Effect in Targeting Market : An descriptive analytical study for a sample of industrial companies in Iraq) - عبد, نعمة شليبة; حميد, لمى ماجد (Journal of Economics and Administrative Sciences, 2012)
This study deals with segmenting the industrial market as an independent variable and targeting the industrial market as a dependent variable. Since the industrial sector represents one of the most important fundamental pillars to build the economies of countries and their development , the Iraqi industrial sector was chosen as a population for the study . Based on measuring the study variables , identifying them and testing the correlation and effect on each other , the study reached a group of findings:1- Increasing the level of availability of study variables inside the companies “The study sample”.2- There is a correlation between the independent variables “ segmenting the industrial market and targeting the industrial market “ .3-There is an effect of segmenting the industrial market on targeting the industrial market .4-There is on difference in the opinions and attitudes of “the study sample” among the companies concerning with segmenting the industrial market and its sub-dimensions , but there is difference in the opinions and attitudes of “the study sample” concerning with targeting the industrial market and its sub-dimensions.  Based on these findings , recommendations were given , in addition to suggestion to conduct studies in future that strengthen the aspects of these subjects.